DEVELOPMENT OF SCIENTIFIC LITERRACY BASED MULTIPLE CHOICE QUESTIONS ON THE CONCEPT OF MOLE - Ratnawati Ratnawati; M Nasir; Muhammad Nazar (Chimica Didactica Acta, 2020)
Research has been conducted on "the development of multiple choice questions based on scientific literacy on the concept of mole material". The purpose of this study was to find out how to develop questions based on scientific literacy on the concept of the mole, how to test the validity, reliability of questions based on scientific literacy and how students respond / respond to multiple choice questions based on scientific literacy. The type of research used is research and development (R D) with a 4-D development model (define, design, develop, and disseminate). The target subjects in this study are Chemistry FKIP students. Data collection techniques using questionnaires, interviews and test results. The research instrument used was an interview sheet, a questionnaire sheet and a multiple choice question sheet based on scientific literacy with a total of 20 questions that had been validated by 2 validators. The results of qualitative data validity analysis from the validation of the items, the percentage of each was above 80% with very high criteria and declared valid and the questions were feasible to use. While the quantitative data validity analysis the resulting percentage as a whole is 65% low category, 25% moderate category and 10% high category with a reliability coefficient value of 0.828 including very high and reliable categories. The results of the analysis of the responses obtained an average value of 78, meaning that the 30 students were more dominant in giving a positive response to the questions.